Towards a framework for the development of e-skills for digital inclusion in the Western Cape - Pokpas, Carlynn (University of the Western Cape, 2015)
Magister Commercii (Information Management) - MCom(IM) === Digital inclusion, through the development of appropriate e-skills, is widely recognised as an essential means of capitalising on the opportunities presented by the information age for social and economic advancement. However, South Africa has not yet clarified its policy of digital inclusion. It has only just begun to tackle the challenge of developing an e-skilled society. As yet there is not an enabling e-skills framework and national implementation strategies are still at an early stage. The conceptual framework for the delivery of e-skills for digital inclusion specifically in the Western Cape of South Africa, which was developed as part of this study, could therefore make a substantial contribution to local research. Certain areas surveyed in this study have been overlooked, underestimated or have yet to be explored by local researchers, while existing research on related areas is generally fragmented and studied in isolation, despite the high interrelationship between the various areas. The conceptual framework that has been compiled offers a coherent holistic perspective, and depicts the logical flow from digital exclusion to inclusion in the Western Cape context. It identifies: (i) the groups most in need of focused inclusion efforts; (ii) significant barriers to inclusion; (iii) specific e-skill clusters for digital inclusion; (iv) guidelines for delivering these e-skills; and (v) the objectives of digital inclusion that the Western Cape should strive to attain. Each of these research areas has been investigated in the context of an on-going provincial e-skills for digital inclusion initiative, focused on training (largely marginalised) community e-centre employees. The qualitative research used semi-structured interviews with ten recently trained individuals, as well as three programme facilitators. Overall, digital inclusion in the Western Cape is conceived as a gradual process, initially concerned with achieving relatively basic objectives such as enabling citizens to access information and increasing the use of ICT in the province. It is envisioned that these short-term outcomes will eventually translate into longer-term advantages for individuals as well as the larger society. Having the appropriate knowledge and attitudes is as important for digital inclusion as having skills. Therefore the term ‘digital competence’ is preferable to ‘e-skills’. The competence areas include combinations of technical and cognitive abilities, the latter being more relevant to the broader inclusion impacts, yet more challenging to instil. These findings, which have been combined with strongly learner-centred guidelines, are presented in the conceptual ‘Digital Competence for Digital Inclusion’ framework. It is hoped that curriculum developers will give serious consideration to this framework and the recommendations contained in this study. It could form a useful basis for the development of digital inclusion throughout the country and e-skills related academic research.